2006
DOI: 10.1073/pnas.0511289103
|View full text |Cite
|
Sign up to set email alerts
|

Combined top-down and bottom-up proteomics identifies a phosphorylation site in stem–loop-binding proteins that contributes to high-affinity RNA binding

Abstract: The stem-loop-binding protein (SLBP) is involved in multiple aspects of histone mRNA metabolism. To characterize the modification status and sites of SLBP, we combined mass spectrometric bottom-up (analysis of peptides) and top-down (analysis of intact proteins) proteomic approaches. Drosophilia SLBP is heavily phosphorylated, containing up to seven phosphoryl groups. Accurate Mr determination by Fourier transform ion cyclotron resonance (FTICR)-MS and FTICR-MS top-down experiments using a variety of dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 38 publications
8
61
0
Order By: Relevance
“…S1A). dSLBP-EPNK bound to stem-loop RNA threefold more tightly than nonphosphorylated dSLBP RPD-WT, in accordance with a previous report where phosphorylation of the TPNK motif increased binding affinity sevenfold (16). dSLBP RPD-4E bound to stemloop RNA 12-fold more tightly than did dSLBP RPD-WT.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S1A). dSLBP-EPNK bound to stem-loop RNA threefold more tightly than nonphosphorylated dSLBP RPD-WT, in accordance with a previous report where phosphorylation of the TPNK motif increased binding affinity sevenfold (16). dSLBP RPD-4E bound to stemloop RNA 12-fold more tightly than did dSLBP RPD-WT.…”
Section: Resultssupporting
confidence: 91%
“…This RNAprocessing domain (RPD) is necessary and sufficient for histone mRNA 3′-end processing in vitro (15). The RBDs of human SLBP (hSLBP) and Drosophila SLBP (dSLBP) are phosphorylated at a Thr residue in a conserved TPNK motif (16,17). The recent crystal structure of hSLBP RBD in complex with histone mRNA stem loop and 3′ hExo, a 3′-5′ exonuclease required for histone mRNA degradation, provided the first molecular insights into the architecture of this complex, and revealed how the hSLBP RBD forms a new RNA-binding motif to interact with the stem-loop RNA (18).…”
mentioning
confidence: 99%
“…Thus, the fluorescence anisotropy and the mobility shift assays suggest that Pin1 and a phosphatase such as PP2A can act to increase the off-rate of SLBP from the stem-loop at the 3= end of histone mRNA, allowing exchange of labeled and unlabeled RNA in the complex. The results are consistent with our published studies (3,65) showing that SLBP that is dephosphorylated at Thr171 has a higher off-rate for the histone mRNA stem-loop.…”
Section: Structural Basis For the Phosphorylated Slbp-pin1 Interactionsupporting
confidence: 93%
“…We have recently shown that SLBP undergoes proline isomerization about a conserved phosphorylated Thr-Pro sequence in its RNA binding domain (RBD) (3,29,65). There are six Ser-Pro/Thr-Pro sequences in human SLBP, all of which have been previously shown to be phosphorylated by mass spectrometry (12).…”
mentioning
confidence: 99%
“…A common design goal in recent instruments is the improvement of both duty cycle and dynamic range through selective accumulation of ions from the source during the time necessary to record the FT-ICR spectrum. Q/FT-ICR instruments are now available commercially from two vendors, Bruker Daltonics [67] and Varian [68].…”
Section: Beam-trap Hybrid Instrumentsmentioning
confidence: 99%